Vom Germanenerbe zum Urkommunismus : Urgeschichtsbilder in Museen der SBZ und DDR - Lindemann, Arne 1976- (De Gruyter, 2022)
After the end of the World War II, the museums in the Soviet Occupation Zone (SBZ) and the GDR were faced with the task of mastering the narrative turn from an ethnic-nationalist conception of prehistory to a Marxist one. Using an extensive body of exhibition photos, this volume analyses the depiction of prehistory in museums of the SBZ and the GDR as well as discourses that led to the alteration or persistence of conceptions of history